1H‐NMR, Photophysical, and pH Studies of 4‐(4, 5‐Diphenyl‐1H‐imidazol‐2‐yl)benzaldehyde through Experimental and DFT Theoretical Analysis. Issue 1 (7th January 2020) - Anandhan, Karnambaram; Cerón, Margarita; Ceballos, Paulina; Ramos‐Hernández, Rodrigo; Perumal, Venkatesan; Pérez‐Gutiérrez, Enrique; Sosa‐Rivadeneyra, Martha; Thamotharan, Subbiah; Percino, M. Judith
Abstract: In the present study the molecular structure of compound 4‐(4, 5‐diphenyl‐1 H ‐imidazol‐2‐yl)benzaldehyde [DPI‐BA ] and its optoelectronic properties are reported. The SCXRD analysis revealed that DPI‐BA crystallizes in the Orthorhombic crystal system and P ca21 space group with Z=4. The intermolecular N‐H⋅⋅N interaction generates a one‐dimensional chain. An interesting halochromic behavior was observed for the DPI‐BA in THF:H2 O (9:1) by varying the pH analysis. The fluorescence properties of neutral and acid‐base solutions were monitored by UV‐vis and 1D, 2D‐NMR studies. The HCl vapor was bubbled to the DPI‐BA in the DMSO‐d6 solution and the corresponding fluorescence wavelength changed from green (λem 501 nm) to blue (λem 459 nm). In the case of a basic pH solution was made by adding NaOH flakes to the DPI‐BA DMSO‐d6 solution and then the fluorescence wavelength changed from green to orange (λem 595 nm). The λmax of PL emission could be correlated to intermolecular charge transfer (ICT). The optical absorption and cyclic voltammetry measurement were performed to determine the bandgap. Besides, the quantitative analysis of intermolecular interactions through PIXEL, QTAIM, NBO, GIAO‐DFT methods and DFT studies was correlated to the experiments. Abstract : 4‐(4, 5‐diphenyl‐1 H ‐imidazol‐2‐yl)benzaldehyde (DPI‐BA) crystallized in the Orthorhombic crystal system, P ca21 space group with Z=4. The photophysical properties of DPI‐BA was studied. The fluorescence properties of neutral and acid‐base solutions were monitored by UV‐vis, emission and 1D, 2D NMR analysis. Besides, the quantitative analysis of intermolecular interactions through PIXEL, QTAIM, NBO, and TD‐DFT studies were correlated to the experiments.